THE EFFECT OF PSYCHOEDUCATION ON ANXIETY AND STRESS LEVELS IN PROLANIS PATIENTS AT HEALTH CENTER - Jennifa, Jennifa (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction : Anxiety and stress are common among chronic disease patients, especially those who are in the Chronic Disease Care Program / Prolanis, namely, type-2 diabetes mellitus and hypertension. Psychoeducational therapy can reduce the level of anxiety and stress in Prolanis patients. This research aims to identify the influence of psychoeducation therapy to the anxiety and stress level in Prolanis patients at Manisrenggo I Health Center.Method : This research used a pre-experiment method with one group pre-test post-test design approach. The respondents of this research were 30 Prolanis patients taken using a purposive sampling technique. The data were collected by means of ‘depression anxiety and stress scale’ (DASS) instruments which consists of 42 items. The data collected were analyzed using Wilcoxon signed-rank test.Result : The research results showed that there was an influence from psychoeducation to the reduction of anxiety and stress in Prolanis patients at Manisrenggo I Health Center. Wilcoxon signed-rank analysis showed a significant level p = 0.05, where p-value = 0.000, therefore p < 0.05. Conclution : (1) Most of the respondents experienced anxiety and stress at a medium level during pre-test; (2) Most of the respondents experienced anxiety and stress at a low level during post-test; (3) There was an influence of psychoeducation therapy to the anxiety and stress level in Prolanis patients at Manisrenggo I Health Center.